Framing Media Online Nusa Bali Tentang Kasus Bunuh Diri Komunitas Hindu Di Bali - I Gede Titah Pratyaksa (Jayapangus Press, 2026)
Framing of Suicide Cases in Online Media and Copycat Suicide Risk Among Balinese Hindus. This study analyzes the framing of suicide reporting on media online Nusa Bali through a Balinese Hindu perspective, applying Entman’s framing analysis to three news articles from Januari-June 2025. The analysis focuses on four dimensions: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Key findings indicate that Problem definition predominantly framed suicides as personal tragedies with limited community-based solutions, causal interpretation emphasized individual-level factors, moral evaluation highlighted prompt evacuation responses by authorities but lacked spiritual perspectives for preventive moral grounding, treatment recommendations focused on structural and preventive measures, practical contributions include proposed media reporting guidelines respecting Hindu values.